Effects of prey metapopulation structure on the viability of black‐footed ferrets in plague‐impacted landscapes: a metamodelling approach. Issue 3 (18th February 2014) - Shoemaker, Kevin T.; Lacy, Robert C.; Verant, Michelle L.; Brook, Barry W.; Livieri, Travis M.; Miller, Philip S.; Fordham, Damien A.; Resit Akçakaya, H.; Stephens, Philip
Summary Species interactions have been largely ignored in extinction risk assessment. However, the black‐footed ferret Mustela nigripes exemplifies a class of endangered species for which strong species interactions cannot be ignored. This species is an obligate predator of prairie dogs Cynomys spp., and sylvatic plague Yersinia pestis epizootics threaten to undermine recovery efforts by functionally eliminating the prey base. Multispecies 'metamodelling' techniques offer new opportunities for exploring population dynamics under strong species interdependencies and disease. To investigate ferret extinction risk in plague‐affected landscapes, we simultaneously modelled plague epidemiological processes, prairie dog metapopulation dynamics and ferret demographic responses. Ferret population dynamics were investigated at an important release site (Conata Basin in South Dakota) and for 500 artificial prey landscapes spanning a wide range of realistic colony configurations (e.g. total area, # colonies, spatial clustering) and demographic characteristics. Our simulation models indicate that ferrets are unlikely to persist through episodes of plague at Conata Basin unless they can access prey resources from a wider region or unless management actions can otherwise substantially reduce plague transmission. We show that large, diffuse prairie dog metapopulations (those with colonies spread over a region >2500 km2) are most likely to support ferret populations in plague‐affected landscapes. Our results also highlight the potential importance of metapopulation connectivity in fuelling plague epizootics and thereby imperilling black‐footed ferret conservation efforts. We describe a cycle (c. 5‐ to 25‐year period) of plague‐driven population crashes that is an emergent property of our models, and which can destabilize ferret populations. Synthesis and applications. On the basis of our models, we conclude that few North American prairie dog complexes cover sufficient land area to sustain black‐footed ferret populations through plague‐driven crashes in prey abundance. Consequently, our results underscore the importance of working with many constituents to conserve large prairie dog landscapes in addition to continued development of plague mitigation tools. In addition, the strong relationship between plague‐induced oscillatory prey cycles and predator population persistence highlights the potential conservation benefits of imposing strategic barriers to connectivity in areas over which plague outbreak cycles are strongly synchronous.